2021
DOI: 10.3847/1538-4357/abe710
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced X-Ray Emission from the Most Radio-powerful Quasar in the Universe’s First Billion Years

Abstract: We present deep (265 ks) Chandra X-ray observations of PSO J352.4034−15.3373, a quasar at z = 5.831 that, with a radio-to-optical flux ratio of R > 1000, is one of the radio-loudest quasars in the early universe and is the only quasar with observed extended radio jets of kiloparsec scale at z ≳ 6. Modeling the X-ray spectrum of the quasar with a power law, we find a best fit of Γ = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 98 publications
1
15
0
Order By: Relevance
“…Notably, the two quasars with the brightest [CII] emission in our sample are also the brightest X-ray sources known at z 6 (Medvedev et al 2020(Medvedev et al , 2021. Their intrinsic X-ray radiation could be lower because X-ray luminosity can be enhanced by the inverse Compton scattering of the CMB photons by electrons in the jets, which is particularly important at high redshift (e.g., Ighina et al 2021b;Connor et al 2021;Medvedev et al 2021). Nevertheless, the observed high X-ray luminosities of these two quasars can be an indication of a higher XDR contribution to the [CII] emission than in quasars with moderate or low X-ray luminosities.…”
Section: Rojasmentioning
confidence: 86%
“…Notably, the two quasars with the brightest [CII] emission in our sample are also the brightest X-ray sources known at z 6 (Medvedev et al 2020(Medvedev et al , 2021. Their intrinsic X-ray radiation could be lower because X-ray luminosity can be enhanced by the inverse Compton scattering of the CMB photons by electrons in the jets, which is particularly important at high redshift (e.g., Ighina et al 2021b;Connor et al 2021;Medvedev et al 2021). Nevertheless, the observed high X-ray luminosities of these two quasars can be an indication of a higher XDR contribution to the [CII] emission than in quasars with moderate or low X-ray luminosities.…”
Section: Rojasmentioning
confidence: 86%
“…Eilers et al (2017) originally noted that J0100+2802 has an unusually small proximity zone (R p = 7.1 proper Mpc, or a luminosity-corrected R p,corr = 3.1 proper Mpc). Such a small zone size could imply a short quasar lifetime (t < 10 5 yr) -compared to values of t > 10 6 yr seen at this epoch in other proximity zone measurements (Eilers et al 2017) and from jet lifetimes (Connor et al 2021) -or that the intrinsic quasar luminosity is less than what is observed.…”
Section: Introductionmentioning
confidence: 66%
“…Notably, the two quasars with the brightest [CII] emission in our sample are also the brightest X-ray sources known at z 6 (Medvedev et al 2020(Medvedev et al , 2021. Their intrinsic X-ray radiation could be lower because X-ray luminosity can be enhanced by the inverse Compton scattering of the CMB photons by electrons in the jets, which is particularly important at high redshift (e.g., Ighina et al 2021;Connor et al 2021;Medvedev et al 2021). Nevertheless, the observed high X-ray luminosities of these two quasars can be an indication of higher XDR contribution to the [CII] emission than in quasars with moderate or low X-ray luminosities.…”
Section: The Effects Of the Jet On Star Formationmentioning
confidence: 86%

The [CII] and FIR properties of z>6 radio-loud quasars

Khusanova,
Bañados,
Mazzucchelli
et al. 2022
Preprint
Self Cite